The Impact of Economic Growth, Unemployment and Inflation on Informal Employment in Turkey: an ARDL Bounds Test Approac - Rümeysa Çelik; Abdurrahman Keskin; Abdulkadir Keskin (Sosyal Siyaset Konferansları Dergisi)
The globalization of the economy has caused the use of informal labor in many sectors and countries. Policies and measures to solve this problem have been attempted, but informal employment has become a difficult problem to solve, both worldwide and in Turkey. Changes in macroeconomic factors impact informal employment, in addition to policies toward informal employment. The aim of this study is to reveal the relationship between economic growth, unemployment and inflation with informal employment. For this purpose, the long-term and short-term relationships of economic growth, unemployment, and inflation indicators on informal employment have been analyzed. In this study, quarterly data collected from CBRT and TurKStat for the years 2004-2020 has been utilized. The long and short term effects of the factors determined on informal employment were analyzed using the ARDL bounds test. All of the long term coefficients are statistically significant. There is a long-term relationship between economic growth, unemployment, inflation and informal employment. CointEq (-1) 45% of the imbalances that occur in the short term disappear. According to the empirical results, it is expected that a 1unit increase in economic growth and inflation will create a decrease of 0.233 and 0.039, respectively. 1 unit of increase in unemployment is expected to create an increase of 0.991 on informal employment.